Therapeutic management of inflammatory bowel disease in real‐life practice in the current era of anti‐TNF agents: analysis of the French administrative health databases 2009–2014. Issue 1 (26th October 2016) - Kirchgesner, J.; Lemaitre, M.; Rudnichi, A.; Racine, A.; Zureik, M.; Carbonnel, F.; Dray‐Spira, R.
Summary: Background: Management of inflammatory bowel disease (IBD) has evolved in the last decade. Aim: To assess IBD therapeutic management, including treatment withdrawal and early treatment use in the current era of anti‐TNF agents (anti‐TNFs). Methods: All patients affiliated to the French national health insurance diagnosed with IBD were included from 2009 to 2013 and followed up until 31 December 2014. Medication uses, treatment sequences after introduction of thiopurine or anti‐TNF monotherapies or both (combination therapy), surgical procedures and hospitalisations were assessed. Results: A total of 210 001 patients were diagnosed with IBD [Crohn's disease (CD), 100 112; ulcerative colitis (UC), 109 889]. Five years after diagnosis, cumulative probabilities of anti‐TNF monotherapy and combination therapy exposures were 33.8% and 18.3% in CD patients and 12.9% and 7.4% in UC patients, respectively. Among incident patients who received thiopurines or anti‐TNFs, the first treatment was thiopurine in 69.1% of CD and 78.2% of UC patients. Among patients treated with anti‐TNFs, 45.2% and 54.5% of CD patients and 38.2% and 39.9% of UC patients started monotherapy and combination therapy within 3 months after diagnosis, respectively; 31.3% of CD and 27.1% of UC incident patients withdrew from thiopurine or anti‐TNFs for more than 3 months after their first course of treatment. Five years after diagnosis, the cumulative risks of first intestinal resection in CD patients and colectomy in UC patients were 11.9% and 5.7%, respectively. Conclusions: Step‐up approach remains the predominant strategy, while exposure to anti‐TNFs is high. Surgery rates are low. Treatment withdrawal in IBD is more common than expected.